Effect of increasing temperature on growth performance and survival rate ClownFfish (Ampihiprion ocellaris - Syazili, Aras; M. Samadan, Gamal; Ahmad, Khamsiah; Senen, Jusmiati; Irfan, Muhammad (Agrikan Jurnal Agribisnis Perikanan, 2022)
One of the model fish used in climate change research is clown fish (A. ocellaris). The purpose of this research is to determine the effect of temperature increases on the growth and survival of clown fish. The experiment was carried out in a laboratory with a completely randomized design. The treatments were 28°C, 29°C, 30°C, and 31°C to observe clown fish growth in length and weight, relative growth rate, increased life, and color change over an 8-week period. The treatment temperature resulted in the best growth in length, weight, specific growth rate, and survival. The treatment temperature of 29OC (P0.05) resulted in the best growth in length, weight, specific growth rate, and survival, with values of 1.81 0.09 cm, 1.06 0.15g, 0.78 0. 09%, and 100%, respectively. At 31°C, growth and life were 1.02 0.04cm, 0.18 0.16 g, 0.30 0.04%, and 66.67 5.44%, respectively. At 31 degrees Celsius, the color of Badut fish changed from red to green to blue (P, 0.05). Temperature can cause badut fish mortality and adversely affect their growth.